Students’ Writing Ability And Difficulties In Recount Text Composition - Wilda Nasri; Efri Yoni (Inovasi Pendidikan, 2025)
This study aims to analyze students’ ability and difficulties in writing recount texts at SMP Qu Cahaya Al-Qur’an Padang Panjang. The research employed a qualitative descriptive method involving 11 second-grade students as participants. Data were collected through a recount text writing test and a questionnaire to identify students’ writing difficulties. The assessment focused on two main aspects: generic structure and language features. The findings revealed that students’ overall ability in writing recount texts was categorized as fair. Most students experienced difficulties in organizing ideas, applying correct grammatical structures, and using appropriate vocabulary. Questionnaire results supported these findings, showing that students struggled particularly with language features and grammar usage. These difficulties indicate the need for more focused instructional strategies in teaching recount text writing. The study recommends that teachers provide more guided practice and emphasize the application of generic structure and language features to improve students’ writing skills.